THE CONCEPT OF SYSTEM PARKING IN MEGACITIES - , Е. М., О. А., В. А. (Municipal economy of cities. Series: «Economy science», 2013)
Justified and defined by the needs of the whole system capacity parking central business district of the metropolis. Determined by the rational distribution of the total capacity of individual car parks, as well as the location of the grounded type and appropriate parking.